Tenofovir alafenamide nephrotoxicity in an HIV-positive patient: A case report. Issue 36 (September 2017) - Novick, Tessa K.; Choi, Michael J.; Rosenberg, Avi Z.; McMahon, Blaithin A.; Fine, Derek; Atta, Mohamed G.
Abstract: Rationale: Tenofovir alafenamide (TAF) is novel prodrug of Tenofovir, a nucleotide reverse transcriptase inhibitor. TAF is less nephrotoxic than its predecessor prodrug, tenofovir disoproxil fumarate (TDF). Tenofovir causes mitochondrial dysfunction and tubular injury when there is elevated accumulation in proximal tubule cells. TAF's unique pharmacokinetic profile enables provision of lower required doses for antiviral efficacy. Lower concentrations reach renal tubules minimizing intracellular accumulation and mitochondrial damage. TAF has not been associated with the histologic markers of tenofovir-associated nephrotoxicity that are seen with TDF, such as dysmorphic mitochondria in proximal tubule cells. Here, we report a patient with dysmorphic mitochondria on kidney biopsy after initiating therapy with TAF. Lessons: This case suggests that at risk individuals may experience tubular mitochondrial injury from lower concentrations of tenofovir with TAF.